75 BODY COMPOSITION MEASUREMENTS BY DEXA IN PRETERM INFANTS NEARING DISCHARGE. Issue 1 (1st January 2007) - Ahmad, I.; Coussens, M.; Gallito, S.; Grochow, D.; Cooper, D.
Abstract : Aim: To study the differences in body composition in preterm infants nearing discharge from the NICU and compare them with healthy term newborn infants. We hypothesized that even with optimal nutrition in the NICU, preterm infants close to discharge from the NICU will have differences in body composition measurements compared with term newborn infants. Methods: One hundred infants were recruited prospectively from the NICU and term nursery at UCI Medical Center after IRB approval and parental consent. The infants were recruited in three groups according to gestational age at birth: group 1, 23 to 29 weeks; group 2, 30 to 36 weeks; group 3, 37 to 42 weeks. Anthropometric measurements and whole-body DEXA scans were done when infants were within 1 week of anticipated discharge from NICU or prior to going home from the nursery. Unpaired t -tests were used for statistical analysis and data are expressed as mean ± SEM. Results: Mean adjusted gestational age and measured weights for group 1 ( n = 23) were 38.09 ± 0.42 weeks and 2, 505 ± 109 g; group 2 ( n = 39) were 35.34 ± 0.19 weeks and 2, 253 ± 64.36g; and group 3 ( n = 38) were 39.53 ± 0.22 weeks and 3, 521 ± 82.45 g. Infants in group 2 had decreased percent body fat (6.71 ± 0.72) vs group 1 (9.74 ± 0.99, p = .01) and group 3 (11.88 ± 0.7, p < .0001). Infants in group 1 had similar percent body fat to those in group 3 ( p = .1). However, lean mass and fat mass in group 1 (2, 464.81 ± 82.72g and 318.12 ± 39.98 g) and in group 2 (2, 252 ± 43.55 g and 179.3 ± 26.6 g) were significantly lower than those in group 3 (3, 191 ± 62.56 g and 456.2 ± 38.31 g, p < .0001). Additionally, BMC and BMD in group 1 (40.56 ± 2.56 g and 0.14 ± 0.004 g/cm 2 )) and group 2 (39.59 ± 1.68 g and 0.15 ± 0.003 g/cm 2 ) were significantly lower than in group 3 (73.49 ± 2.05 and 0.20 ± 0.002 g/cm 2, p < .0001). Conclusions: Preterm infants in the NICU who are close to discharge continue to remain smaller than term newborn infants. While preterm infants between 30 and 36 weeks continue to have decreased percent body fat, preterm infants < 30 weeks, who stay longer in the NICU, do catch up and have a percent body fat similar to newborn term infants. However, bone mineralization in preterm infants continues to be a problem despite advances in nutritional strategies in the NICU. Preterm infants nearing discharge continue to have significantly decreased bone mineral content and bone mineral density.